1960
DOI: 10.1063/1.1735840
|View full text |Cite
|
Sign up to set email alerts
|

Growth from the Melt. I. Influence of Surface Intersections in Pure Metals

Abstract: The solid-liquid interface shape during growth from the melt has been determined for pure materials in the vicinity of external and internal surfaces; both the cases of isotropy and anisotropy of solid-liquid interfacial energy have been considered. From these considerations it is possible to determine some effects associated with interface and external surface anisotropy. For example, a preferred direction of growth, a surface layer phenomenon and stray-crystal formation during seeding and normal crystal grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(53 citation statements)
references
References 8 publications
0
52
0
Order By: Relevance
“…Equation (7) is similar to one widely use to determine the liquid-solid surface tension of classical systems, in experiments where gravity is replaced by a temperature gradient [57,58].…”
Section: The Grain Boundary Energymentioning
confidence: 99%
“…Equation (7) is similar to one widely use to determine the liquid-solid surface tension of classical systems, in experiments where gravity is replaced by a temperature gradient [57,58].…”
Section: The Grain Boundary Energymentioning
confidence: 99%
“…In order to accommodate the energy of the twin plane, it has been suggested that the shape of the tip of twinned dendrites must be modified with respect to the paraboloid needle shape typically observed for regular dendrites. Based on previous works aimed at measuring the solid-liquid interfacial energy in transparent systems [11,12], and treating the two lamellae as two different grains with a strong crystallographic relationship in a low tilt angle boundary, first Chalmers [13], then more specifically Eady and Hogan [14], suggested that the tip would develop a re-entrant angle or a "cusp" in order to satisfy the Smith equation (which is equivalent to the Young-Laplace equilibrium condition at a triple junction) along the triple line (twinned solid/untwinned solid/liquid). This condition is given by:…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the factors controlling the variation in a o has been published by Bolling and Tiller (1960) for the case where the solute transfer in the liquid ahead of the advancing interface is by diffusion only. Although the final form of the analysis is approximate, the physical reasoning behind the analysis is clear.…”
mentioning
confidence: 99%